THE RELATIONSHIP BETWEEN SOCIOECONOMIC AND DEMOGRAPHIC FACTORS AND RHEUMATIC HEART DISEASE AT DR. SOETOMO GENERAL HOSPITAL: - - Kevin Ebenhaezer Silaen; Achmad Lefi; Pirlina Umiastuti; Dian Paramita Kartikasari (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Rheumatic heart disease (RHD) is a public health problem, especially among low-income populations in developing countries. This study aims to examine the relationship between demographic and socioeconomic factors and the incidence of RHD at Dr. Soetomo General Hospital, Surabaya. This is an analytic study using a cross-sectional approach, with 284 respondents in 2024. Primary data were collected through questionnaires and analyzed using SPSS. The Chi-Square test revealed a significant relationship between age and RHD (p = 0.000 < 0.005), particularly among individuals aged 40-59 years. Other variables, such as gender, residential area, population density, and economic status, did not show a significant association. These findings underscore the need for targeted public health interventions specifically designed for specific age groups. Further research is recommended, utilizing larger sample sizes and a more detailed classification of RHD severity levels, to enhance prevention and disease management strategies.